2022
DOI: 10.3390/app122010217
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Previous Root Canal Filling Material for Retreatment: Implications and Techniques

Abstract: Adequate removal of the previous filling material may be pivotal to a favorable outcome of root canal retreatment of teeth with post-treatment periodontitis in order to permit the access of irrigants and medicaments to persistent bacteria. However, even with recent technological advances, including the introduction of specially designed instruments, no technique has been shown to predictably promote complete filling removal. Supplementary approaches used after chemomechanical preparation, including the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…The absence of significant differences between the systems for extrusion and intracanal removal of filling material may also be associated with the standardized conditions of root canal anatomy, irrigation and working length (Alves et al., 2022). In these conditions, studies have shown that differences in taper, tip and cross sectional shape, as well as the operation mode and the number of instruments used, fail to promote significant differences in filling extrusion and removal (Alves et al., 2014; de Siqueira et al., 2016; de Souza et al., 2015; Nevares et al., 2017; Rios Mde et al., 2014; Rödig et al., 2014; Silveira et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of significant differences between the systems for extrusion and intracanal removal of filling material may also be associated with the standardized conditions of root canal anatomy, irrigation and working length (Alves et al., 2022). In these conditions, studies have shown that differences in taper, tip and cross sectional shape, as well as the operation mode and the number of instruments used, fail to promote significant differences in filling extrusion and removal (Alves et al., 2014; de Siqueira et al., 2016; de Souza et al., 2015; Nevares et al., 2017; Rios Mde et al., 2014; Rödig et al., 2014; Silveira et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most critical and challenging steps during root canal retreatment is removing the previous filling material, because of the risk of accidents such as zip, deviations and extrusion of debris (Alves et al., 2022). Extruded debris can lead to post‐operative pain, flare‐up or even compromise the long‐term healing of apical periodontitis (Siqueira, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The CBCT evaluation demonstrated that the presence of the remnants is predominantly localized into the lingual and buccal sides of the root canals. Previous studies have demonstrated the presence of a large amount of remnants corresponding to the roots apical third [24,25], suggesting that the conventional manual or rotary systems used to remove filling materials may induce the formation of an apical critical area [25]. In a similar way, remnants may still also be detectable using a self-adjusting file (SAF) and a hollow, compressible NiTi instrument, through which a continuous flow of an irrigant can be provided [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, supplementary techniques have been proposed to increase the cleanliness of root canals during retreatment. Considering the limitations of instruments in removing filling material from the root canal, newer approaches as supplementary steps are currently being proposed [ 12 ]. The XP-Endo Finisher (XPF; FKG Dentaire, La Chaux-de-Fonds, Switzerland) has recently been shown to enhance the removal of root canal fillings [ 13 ].…”
Section: Introductionmentioning
confidence: 99%